Cryopreservation in Eukaryotes - Marco-Jiménez, Francisco; Akdemir, Hülya (IntechOpen, 2016)
Since accidentally discovering the ability of glycerol on protecting cells from freezing damage, many researchers have been pursuing to develop cryopreservation methods of a very wide range of cells and some tissues, and these have found widespread applications in biology and medicine. From the point of view of living organisms, cryopreservation is a useful tool for ex situ conservation of genetic resources together with its contribution on conservation of their biodiversity. Cryopreservation in Eukaryotes includes totally 12 chapters, which have been written by the expert researchers in the field. The chapters are a comprehensive collection of the most frequently used methods for eukaryotes. With this book, every researcher will better understand the principles, background, and current status of cryopreservation in particular organisms.